Description of Family Support on the Motivation of Heart Failure Patients in Undergoing Treatment - Wulan Sari; Beti Kristinawati (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Chronic disease is a condition that causes a person to be hospitalized. One of the chronic diseases is heart failure. Heart failure is more common in older people with weakened heart chambers responsible for pumping blood throughout the body. This study aimed to determine the description of family support on the motivation of heart failure patients in undergoing treatment. This research is descriptive quantitative with cross-sectional research design. This research was conducted at the cardiac polyclinic at Sebelas Maret University Hospital, Sukoharjo Regency. The research was conducted in March-April 2023. The population in this study were all patients with heart failure at the heart polyclinic at UNS Hospital, totaling 1.114. The sample for this study was 294 respondents. The sampling technique used purposive sampling technique. Data collection in this study used the Family Support questionnaire and the Client Motivation For Therapy Scale. Analysis of this research data with descriptive univariate analysis. The results of this study were family support for the motivation of heart failure patients in undergoing treatment at the heart polyclinic, the majority of whom were 160 (54.4%) women, 140 (47.6%) aged 51-65 years, had high school/vocational high school education. 108 respondents (36.7%), the majority suffered from illness for 1-5 years, 182 respondents (61.9%) and the New York Heart Association classification in patients with heart failure, the majority of NYHA II, were 150 respondents (51.0%). The level of family support for heart failure patients undergoing treatment in the good category was 269 (91.5%), and the level of motivation was 147 (50.0%). For people with heart failure, it is hoped that they will have the motivation to take treatment that improves and is supported by the family so that it does not become a burden but can provide and increase knowledge through education to increase motivation for treatment.Keywords: Family Support, Heart Failure, Treatment motivation